What’s so American about Irish independence? Review of Ireland’s Exiled Children - Szedmina, Lívia (AMERICANA E-journal of American Studies in Hungary, 2018)
Ireland’s Exiled Children Robert Schmuhl New York, United States of America: Oxford University Press, 2016 232 pages ISBN: 978-0190224288